2001
DOI: 10.1002/j.2161-007x.2001.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Religion and Spirituality in Marriage and Family Counseling

Abstract: In the fields of counseling and psychology, interest in religious and spiritual issues is expanding. The authors examined integrating religion and spirituality with marriage and family counseling. They explored potential obstacles and negative consequences for this integration, as well as clinical implications. The positive impact of incorporating a religious or spiritual perspective into clinical practice i s discussed. Ethical considerations, techniques, and strategies are presented.ccording to a 1991 Gallup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…A literature review by Dyson, Cobb, and Forman (1997) revealed several themes common to different conceptualizations of spirituality: a search for meaning in life, the need for hope, relatedness or connectedness to others, a set of religious or non-religious beliefs, and expression of spirituality in multiple ways. Other researchers who are writing on the construct of spirituality seem to refer to spirituality as having to do with four different phenomena: (1) an internal belief system (c.f., Burkhart & Solari-Twadell, 2001;Cook et al, 2000;Emmons & Crumpler, 1999;Hawks, 1994), (2) the construction of meaning (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Erickson, Hecker, Kirkpatrick, Killmer, & James, 2002;Shafranske & Gorsuch, 1984), (3) a relationship (c.f., Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Dyson et al, 1997), and (4) a higher power or an ultimate reality (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Sigmund, 2002;Wolf & Stevens, 2001). Along with religiousness and spirituality, the term faith sometimes also appears in the literature to describe similar phenomena.…”
Section: Weaknesses In Previous Clinical Judgment Faith Bias Studiesmentioning
confidence: 99%
“…A literature review by Dyson, Cobb, and Forman (1997) revealed several themes common to different conceptualizations of spirituality: a search for meaning in life, the need for hope, relatedness or connectedness to others, a set of religious or non-religious beliefs, and expression of spirituality in multiple ways. Other researchers who are writing on the construct of spirituality seem to refer to spirituality as having to do with four different phenomena: (1) an internal belief system (c.f., Burkhart & Solari-Twadell, 2001;Cook et al, 2000;Emmons & Crumpler, 1999;Hawks, 1994), (2) the construction of meaning (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Erickson, Hecker, Kirkpatrick, Killmer, & James, 2002;Shafranske & Gorsuch, 1984), (3) a relationship (c.f., Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Dyson et al, 1997), and (4) a higher power or an ultimate reality (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Sigmund, 2002;Wolf & Stevens, 2001). Along with religiousness and spirituality, the term faith sometimes also appears in the literature to describe similar phenomena.…”
Section: Weaknesses In Previous Clinical Judgment Faith Bias Studiesmentioning
confidence: 99%
“…Spiritually oriented psychotherapy is already used in clinical practice, but it is still at the beginning of its history and there are many issues to be investigated (Wolf & Stevens, 2001). While a considerable accumulation has begun to emerge in the worldwide literature in this area, it can be said that the practice of spiritually oriented therapy for Turkey is "in the midst of a stir yet."…”
Section: Resultsmentioning
confidence: 99%
“…Psychological wellbeing has been found to correlate positively with a variety of indicators of psychological adjustment and overall wellness. For example, social adjustment, possession of strong coping skills and resiliency in times of stress and personal crises have all been linked to higher level of psychological wellbeing (Wolf and Stevens, 2001;Kamya, 2000).…”
Section: Introductionmentioning
confidence: 99%